IMPLEMENTATION OF CRIMINAL ELECTION LAW ENFORCEMENT AGAINST VOTING RIGHTS ABUSE PRACTICES IN PALANGKA RAYA CITY IN 2024 - Putriyani; Ivans Januardy; Claudia Yuni Pramita; Istani (International Journal of Cultural and Social Science, 2026)
This research discusses the implementation of criminal law enforcement against the abuse of voting rights based on Law Number 7 of 2017 and the obstacles faced by the Palangka Raya City Election Supervisory Board (Bawaslu) in the 2024 elections. Using an empirical juridical method thru literature study and interviews, the research found that Bawaslu has handled cases of vote misuse, including double voting by two students, thru the Gakkumdu Center mechanism in accordance with legal procedures. However, the effectiveness of law enforcement is still hindered by time constraints in handling cases, a lack of evidence, low public legal awareness, and suboptimal support in technology and budget for training and political education. This research emphasizes the importance of strengthening institutional capacity, budgetary support, enhancing monitoring technology, and community participation to make election oversight and law enforcement more effective and integrity-driven.